Implantação de cemitérios: impacto ambiental nos recursos hídricos, medidas preventivas e mitigadoras: um estudo de caso em Macapá - AP - Brasil - CUNHA, Maria Eleonora de Souza (2019)
Cemeteries can be contamination sources of the superficial water and groundwater through the necrochorume, the liquid of the corpses decomposition, what can be a risk for public health. The aim of this study is to show the connection between cemeteries and possible contamination of water resources through a case study in the city of Macapá-AP. The research involved bibliography survey and field work composed of geologic and hydrologic research in an area selected for a project of a cemetery construction in the north of Macapá. The topographic map, the geological descriptions of the underground material and the map of groundwater flow of the site have been made. All this allowed an analysis of the feasibility of the project by showing data such as the geological configuration of the area and the direction of the groundwater flow from east to west, along with the probability of the aquifer recharge zone being located in the northeast of the site. The results of the studies were favorable for the project as long as the area for the burials is located in the east-central part of the site where topographic elevation is above 9,0 meters and the water table depth is greater than 4,0 meters. The analysis of the vulnerability of the upper aquifer by the GOD method showed a 0,048 result, which means a low level of vulnerability, what is positive for the project. It is recommended that the project have an adequate and efficient drainage system in all its area, and that the wells constructed for the researches turn into groundwater monitoring wells for continuous record of the groundwater quality.For public policies it is recommended that Resolutions CONAMA 335/2003 and 368/2006 be respected and that each place have its own Terms of Reference for this kind of project, considering its physiographic, geologic and hydrologic features, for the purpose of the environment protection.